Conservative Management After a Single Fetal Death in a Dichorionic Diamniotic Twin Pregnancy and Fetus Papyraceus: A Case Report - Rayra Amana Macêdo Maciel; Caio Ribeiro Vieira Leal; Marina Fistarol; Sara de Pinho Cunha Paiva; Moisés Salgado Pedrosa; Maria Luiza Peloso Maia (European Medical Journal, 2021)
Multifetal pregnancies are estimated to represent 3.2% of all pregnancies (80% are dichorionic and 20% monochorionic) and are associated with a higher risk of perinatal morbidity and mortality relative to single pregnancies. The authors report a successful case of conservative management of a dichorionic diamniotic twin pregnancy after a single fetal death in the second trimester of pregnancy. The diagnosis was made in the 22nd week of pregnancy and the pregnancy was followed up until delivery in the 39th week. A healthy (2.855 kg) female infant was born and a dead fetus, approximately 20 cm in length and connected by the rudimentary umbilical cord to the small calcified placenta, was seen. The occurrence of a single fetal death is a relatively common event, which has implications for maternal and fetal outcomes. This diagnosis is relevant due to its potential effect on the survival of the other fetus and on possible maternal complications. In order to avoid complications and achieve the optimal maternal and neonatal outcomes, conservative prenatal follow-up should focus on careful monitoring and serial assessment of both fetal and maternal wellbeing. In gestational losses where the fetus is retained intrauterine for at least 10 weeks, there is the possibility of finding fetus papyraceus at the time of delivery. This is a rare event that results from incomplete reabsorption of the dead fetus, which is then compressed between the membranes and the uterine wall.